Perbaikan teknik budidaya jamur sebagai upaya dalam meningkatkan hasil produksi - Gustina Indriati; Yosmet Hidayat; Yasrial Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The not yet maximally the application of mushroom cultivation techniques by the community has been an influence on the results of cultivation. The use of ineffective techniques can prolong working time and high damage to the oyster mushroom block, as experienced by MycoAgro businessman. This activity aims to improve mushroom cultivation techniques in order to increase the production of mushroom businesses owned by the community. This activity was carried out in the Panyalaian Nagari District X Koto, Tanah Datar District, West Sumatra. The method used is in the form of community assistance through counselling and training of partners in improving cultivation facilities, strengthening cultivation techniques that have been and have not been mastered by partners. Making operational standards for cultivation tools and work safety procedures and providing entrepreneurial motivation counselling to partners. The results of the activity showed that there had been an increase in understanding of cultivation techniques controlled by partners. Partners have been able to complete 2000 mushroom blocks with a faster time than before. There has been a division of labour with cultivation locations and work safety procedures. During the process of cultivating bag locks which were damaged only 15%, this number was far smaller than before. The average production of oyster mushrooms is 30.7 kg/week. Partners have produced their own seeds, know the technique of consuming mushroom cultivation besides oyster mushrooms and are able to use growing media other than wood husks. Based on the activities carried out it can be concluded that there has been an increase in the cultivation of oyster mushrooms owned by the community.